PRESENT STOICISM IN SOME LETTERS FROM DESCARTES TO PRINCESS ELISABETH OF BOHEMIA - Ramírez Restrepo, Rubiel (Disertaciones, 2017)
It is rather common in Cartesian literature to talk about the influence of Stoic philosophy in his thinking, especially in the moral aspect. While the third maxim of provisional moral is an obligatory reference point of their approaches, this influence can be traced also in the correspondence, especially in which Descartes had with the Princess Elisabeth of Bohemia, among those letters, stand those submitted by the philosopher in the year 1645, which reveals the presence of Stoic ideas, especially Epictetus and Seneca. However, far from being a mere replica of Hellenistic philosophy in the seventeenth century philosopher, this means a very complex reception process, which is both assimilation of that tradition, as a critical positionbout it.